Current therapy in vascular surgery - Ernst, Calvin B; Stanley, James C (Mosby, 2001)
Univ. of Michigan, Ann Arbor. Primary focus is operative management with nonoperative treatments frequently emphasized. Basic pathophysiology and new diagnostic techniques are included. All chapters are new to this edition and written by new authors. Previous edition: c1995. Halftone illustrations and extensive references.
Keywords: Blood Vessels; cévy; CÉVY - CHIRURGIE; chirurgie; angiologie